An environmentally friendly approach for the synthesis of quinazolinone sulfonamide - Balalaie, Saeed; Rominger, Frank (Monatshefte für Chemie, 2017)
An efficient synthesis of quinazolinone sulfonamide derivatives through four-component reaction is reported. The four-component reaction is based on the reaction of isatoic anhydride, hydrazine hydrate, saccharin, and aromatic aldehydes in the presence of nano-catalyst SBA-Pr-SO3H. Saccharin was used as a novel source of sulfonamide moiety in this reaction.Graphical abstract Open image in new window